A THE SEMANTICS OF VERBAL PHRASEOLOGICAL UNITS AND THEIR EVALUATIVE EMOTIVE PECULIARITIES IN THE ENGLISH AND RUSSIAN LANGUAGES : THE SEMANTICS OF VERBAL PHRASEOLOGICAL UNITS AND THEIR EVALUATIVE EMOTIVE PECULIARITIES IN THE ENGLISH AND RUSSIAN LANGUAGES (Scientific journal of the Fergana State University, 2025)
The article studies the evaluative-emotive nature of the semantics of verbal phraseological units (VPU). The author views the connotative aspect as the stylistic nuance, emotional-expressive element, and enhanced communicative power characteristic of phraseological units. This feature is crucial to phraseological semantics, as the meaning structure of all stable expressions is two-layered and rooted in figurative reinterpretation. Connotation is understood as supplementary information that encompasses evaluative, expressive, emotional, and stylistic-functional elements, granting phraseological units unique importance within speech contexts. The analysis of the factual material found that the evaluative-emotive character is most clearly manifested in phraseological units reflecting actions, activities, and the human condition. Particular attention is paid to the emotive component, which has a pronounced meaning in the thematic group associated with the human condition. The study's results emphasize the importance of evaluative-emotive semantics for understanding the structure and functioning of verbal phraseological units.